A SEMIOTIC CLASSIFICATION OF BRITISH ROAD SIGNS: ANALYZING SYMBOLIC, TEXTUAL AND MULTIMODAL COMMUNICATION (World Bulletin of Social Sciences, 2026)
Traffic signs are essential instruments for road safety, utilizing different semiotic methods to communicate messages to motorists. This research examines an extensive dataset of UK road signs, classifying them into three separate categories: exclusively symbolic, exclusively textual, and multimodal (a combination of both). The findings show that although warning signs depend largely on universal symbols for quick recognition, information and direction signs require a multimodal strategy to deliver precise geographic and regulatory information.